A pseudo point source model based on velocity coupled method for dilute particle-laden flow with dissipation scale particles. (June 2018) - Li, Zhenzhong; Wei, Jinjia; Yu, Bo
Highlights: A pseudo point source model is proposed to take the finite size effect of dissipation scale particles in to consideration. The pseudo point source model behaves better than the conventional point source model in predicting the particle-free settling process. The pseudo point source model can obtain more reasonable results than the conventional point source model when simulating the particle-laden channel turbulence. Abstract: The interphase interaction between the particle and fluid is one of the most fundamental issues in the research of particle-laden flow. Neither the conventional point source model nor the particle-resolved method is an appropriate choice to study the interphase interaction when the order of magnitude of particle diameter is the same as the turbulence dissipation length scale or the grid spacing. In the present study, a pseudo point source model is proposed to consider the finite size effect of particles under the limitation of an acceptable calculation consumption. In this model, the feedback effect of particles on the fluid is represented by coupling the particle-induced disturbance flow with the carrier flow. The disturbance flow of the particle is solved by Stokes approximation or Oseen correction based on the particle Reynolds number, and the geometric relationships between the particle along with its disturbance and grid are also considered. Meanwhile, the no-slip boundary condition on the particle surface is reconstructed as much as possible. The free settling of a single particle and the particle-laden turbulent channel flow are applied to verify the pseudo point source model. For each simulation case, the results of the pseudo point source model are compared with that obtained by the conventional point source model. From the preliminary results, it is concluded that the pseudo point source model behaved much better than the conventional point source model in predicting the free settling process when the particle diameter is greater than the grid spacing. In simulations of the particle-laden channel turbulence, the pseudo point source model can obtain more reasonable results, especially in the cases where the particle diameter is larger than the Kolmogorov dissipation scale. Finally, some outlooks which needs further study are discussed.